Spectrophotometric study of iron oxidation in the iron(II)/thiocyanate/acetone system and some analytical applications - Martins, Fernando Grine; de Andrade, Jose Fernando; Pimenta, Adriano Cesar; Lourenço, Leandro Marangheti; Castro, Jorge Ricardo Moreira; Balbo, Valdir Roberto (Eclética Química, 2005)
The possibility of using thiocyanate to determine iron(II) and/or iron(III) in water-acetone mixture has been re-examined as part of a systematic and comparative study involving metallic complexes of pseudohalide ligands. Some parameters that affect the complete oxidation of the ferrous cations, their subsequent complexation and the system stability have been studied to optimize the experimental conditions. Our results show the viability and potentiality of this simply methodology as an alternative analytical procedure to determine iron cations with high sensitivity, precision and accuracy. Studies on the calibration, stability, precision, and effect of various different ions have been carried out by using absorbance values measured at 480 nm. The analytical curve for the total iron determination obeys Beer’s law (r = 0.9993), showing a higher sensitivity (molar absorptivity of 2.10x10 4 L cm -1 mol -1 ) when compared with other traditional systems (ligands) or even with the “similar” azide ion [1.53x10 4 L cm -1 mol -1 , for iron–III/azide complexes, in 70% (v/v) tetrahydrofuran/water, at 396 nm]. Under such optimized experimental conditions, it is possible to determine iron in the concentration range from 0.5 to 2 ppm (15-65% T for older equipments, quartz cells of 1.00 cm).